TEST ANALYSES OF DAM DEFORMATIONS FOR SECURITY OF PEOPLE AND ENVIRONMENTAL PROTECTION - Sedlak, VladimÃr (European Scientific Journal, ESJ, 2013)
Deformations on buildings and structures due to own weight, water pressure, inner temperature, contraction, atmospheric temperature and earth consolidation occur. Especially, it is necessary to embark on monitoring and analyzing of deformation effects and movements of any sizeable dams and water basins and so to prevent of their prospective catastrophic effects in the environment and also human lives. The paper is centered on the stability of the earthen dam of the Pod Bukovcom near town KoÅ¡ice in the East Slovak Region. Results and analyses of the geodetic terrestrial and GPS measurements on the earthen dam are undergone by to test-statistics, the model of stability or prospective movement of the earthen dam with time prediction. The paper outputs are incorporated into GIS and information system of U.S. Steel KoÅ¡ice.